Eksplorasi Nilai Budaya dan Praktik Sosial Masyarakat Kampung Pasir Jengkol sebagai Sumber Pendidikan Karakter - Miftahudin; Jamilah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to explore cultural values and social practices preserved by the community of Kampung Pasir Jengkol, Talagasari Village, Banjarwangi District, as a source of character education in basic education. The research employed a qualitative descriptive approach using an ethnographic method. Data were collected through participatory observation, in-depth interviews, and documentation involving a traditional leader, a local ritual practitioner, and a young farmer. The results indicate that the community strongly upholds the value of gotong royong (mutual cooperation), reflected in collective activities such as house construction, village road development, and assistance during social and religious events. A distinctive wedding tradition involving collective participation and symbolic gifts strengthens social solidarity. In addition, the memenyan ritual conducted before the rice harvest represents spiritual gratitude and harmony between humans, nature, and God. Regular religious gatherings also contribute to strengthening moral values and social cohesion. These findings demonstrate that local cultural practices in Kampung Pasir Jengkol have significant potential as contextual learning resources for character education in elementary education.